Pengaruh Latihan Pliometrik Terhadap Peningkatan Power Otot Tungkai Atlet Gulat - Swandika Pinem; Irfan Deny Oktavian; Muhammad Fitrah Mubarak; Fachrun Nisa Sofiyah Khasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of plyometric training on increasing leg muscle power in wrestling athletes. The method used was a pre-experiment with a one-group pretest-posttest design, and involved 40 wrestling athletes selected through a purposive sampling technique. The test instrument used in this study was a standing broad jump, and the data were analyzed using normality and homogeneity tests as prerequisite tests, then continued with a paired t-test and calculating the average increase. The results showed that: (1) there was a significant increase in leg muscle power in wrestling athletes, namely 183.55 before treatment and increasing to 186.97 after participating in the plyometric training program; (2) the data in this study were normally distributed and homogeneous; (3) the significance value of the t-test was 0.000 < 0.05, which explains that there is a significant effect. The conclusion of this study is that there is a significant effect of plyometric training on increasing leg muscle power in wrestling athletes. Keywords: Leg Muscle Power, Plyometric Training, Wrestling